Personality disorders and forensic assessments: The benefits of ICD-11. (October 2022) - Carroll, Andrew; Walvisch, Jamie; Marsh, Tim
A recent landmark case in the Australian state of Victoria clariﬁed the ways in which personality disorders may be taken into account when the courts are sentencing convicted offenders. The ruling especially emphasised: the need for evidence to be 'cogent'; the need to determine 'severity' of the personality disorder; the need to consider whether there is a 'connection to the offending'; the need for caution when diagnoses are based solely on behaviour; and the need to consider rehabilitative prospects and community protection. The ruling has significant implications for how forensic experts in all jurisdictions might most effectively assist the courts with the task of sentencing offenders with personality disorders. In this paper we argue that the approach to diagnosis taken in the newly published ICD-11 manual, that eschews 'categories' of personality disorder, in favour of a dimensional model supported by trait theory, is of much greater utility to forensic mental health experts striving to address these issues, compared to traditional 'categorical' approaches.